2024
DOI: 10.1038/s41598-024-54802-6
|View full text |Cite
|
Sign up to set email alerts
|

Directed functional connectivity of the default-mode-network of young and older healthy subjects

Gadi Goelman,
Rotem Dan,
Ondrej Bezdicek
et al.

Abstract: Alterations in the default mode network (DMN) are associated with aging. We assessed age-dependent changes of DMN interactions and correlations with a battery of neuropsychological tests, to understand the differences of DMN directed connectivity between young and older subjects. Using a novel multivariate analysis method on resting-state functional MRI data from fifty young and thirty-one healthy older subjects, we calculated intra- and inter-DMN 4-nodes directed pathways. For the old subject group, we calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Our results demonstrated that the spikes fell outside the wavelet confidence region (defined in Torrence and Compo [18,19]), which were not included in the calculations. This confirmed that the findings were not influenced by wavelet-filtering artifacts [19,20].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Our results demonstrated that the spikes fell outside the wavelet confidence region (defined in Torrence and Compo [18,19]), which were not included in the calculations. This confirmed that the findings were not influenced by wavelet-filtering artifacts [19,20].…”
Section: Resultssupporting
confidence: 85%
“…For bivariate (pair coherence) calculations, we used the phase-lag-index (PLI) [20,21], and for multivariate coherence four-node pathways, we used the pathway-index (PWI) [10][11][12][13][14][15][16]22] (see method). Both calculations employed wavelet analysis with custom-developed software.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations